Experimental Study and Life Prediction of Bolt Loosening Life under Variable Amplitude Vibration. (5th November 2019) - Yang, Guangwu; Che, Chengjian; Xiao, Shoune; Yang, Bing; Zhu, Tao; Jiang, Shilin
Abstract : The transverse vibration test of bolts has been designed with adoption of the fatigue tester to study the features of the loosening life of bolts. Firstly, the transverse vibration frequency has been changed, the effects of the amplitudes of displacement, velocity, and acceleration on the loosening life of bolts have been compared, and it has been confirmed that the transverse displacement amplitude is the main factor that affects bolt loosening in low-frequency vibration. Secondly, the loosening degree of the bolts preloaded standard under five displacement amplitude grades has been monitored and the bolt loosening situation has been expressed through the residual preload-vibration times curve. The data of each stage of residual preload under each displacement amplitude were summarized, and the displacement-life ( D-N ) curve of bolt loosening under different loosening situations (percentage of residual preload) which is referred to the material fatigue life S-N curve was drawn. Finally, the accumulation mechanism of bolt loosening has been studied and the linear accumulation model of bolt loosening has been set up through designing variable amplitude vibration tests at high-low and low-high displacement stages. Results show that, through the bolt loosening D-N curve, it can be found out that the bolt loosening life curve and the material fatigue life curve are with features of double line and high- and low-cycle boundary under the logarithmic coordinate. Linear accumulation of bolt loosening is with similar principle of linear damage accumulation of material fatigue. Therefore, the bolt loosening life can be predicted through bolt displacement-loosening life ( D-N ) curve attained from the experiment and the established linear accumulation model of bolt loosening.